Novel CACNA1A Variant p.Cys256Phe Disrupts Disulfide Bonds and Causes Spinocerebellar Ataxia. Issue 2 (14th October 2021) - Nikonishyna, Yuliia V.; Ortner, Nadine J.; Kaserer, Teresa; Hoffmann, Jessica; Biskup, Saskia; Dafotakis, Manuel; Reetz, Kathrin; Schulz, Jörg B.; Striessnig, Jörg; Dohrn, Maike F.
Abstract: Background: Spinocerebellar ataxia (SCA) is a progressive, autosomal dominant neurodegenerative disorder typically associated with CAG repeat expansions. Objective: We assessed the pathogenicity of the novel, heterozygous missense variant p.Cys256Phe (C256F) in the pore‐forming α1‐subunit of the Cav2.1 Ca 2+ channel found in a 63‐year‐old woman with SCA with no CAG repeat expansion. Methods: We examined the effect of the C256F variant on channel function using whole‐cell patch‐clamp recordings in transfected tsA‐201 cells. Results: The maximum Ca 2+ current density was significantly reduced in the mutant compared to wild‐type, which could not be explained by lower expression levels of mutant Cav2.1 α1‐ protein. Together with a significant increase in current inactivation, this is consistent with a loss of channel function. Molecular modeling predicted disruption of a conserved disulfide bond through the C256F variant. Conclusions: Our results support the pathogenicity of the C256F variant for the SCA phenotype and provide further insight into Cav2.1 structure and function. Abstract : SCA6 is mostly caused by polyglutamine expansions in the Cav2.1 α1‐subunit C‐terminus. This study describes the novel missense mutation C256F in the Cav2.1 α1‐subunit identified in an SCA patient without polyglutamine expansions. The mutation disrupts the conservative disulfide bond causing loss of channel function through decreased current amplitudes and faster inactivation. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society